ANALISIS KEBANGKRUTAN DENGAN MENGGUNAKAN MODEL ALTMAN Z-SCORE PADA PERUSAHAAN ASURANSI YANG GO PUBLIC DI BURSA EFEK INDONESIA ( PERIODE TAHUN 2010 – 2013 ) - ., Syilviana; Rachmawati, Titiek (JEB17 : Jurnal Ekonomi dan Bisnis, 2016)
The insurance company is a non-bank financial institutions which have a role thatis not much different from the bank, which is engaged in the service provided to thecommunity in addressing the risks that will occur in the future. The company wasfounded with the hope of generating profits so that they can survive in the long term forthe infinite. In order for the survival of a company is maintained, then the managementshould be able to maintain or even more spur increased performance. Various analyzeswere developed to predict the beginning of the bankruptcy of the company. One analysisis widely used today is the analysis of Altman Z-Score, which this analysis refers to thefinancial ratios of the company. The purpose of this study was to analyze the bankruptcyof the insurance companies that go public in Indonesia Stock Exchange year period 2010– 2013. This study used a sample of four companies from the insurance sector. Source ofdata is done by using secondary data. The data is processed b the method of the Z-scoreformula Z = 1,2X1 + 1,4X2 + 3,3X3 + 0,6X4 + 1,0X5. With the description of Z < 1,81the company categorized into companies that will be bankrupt, the value Z 1,81 < 2,99then the company is considered to be in the grey area of bankrupt enterprises thepossibility area and some are not, and the value of Z > 2,99 then the company is in a veryhealthy state so that the probability of bankruptcy is very little going on. In general, theresults of these studies indicate that the four insurance companies namely PT AsuransiBintang year 2010 value of Z = 0,798 year 2011 value of Z = 1,212 year 2012 value of Z= 1,732 year 2013 value of Z = 1,819, PT Asuransi Harta Aman Pratama year 2010 valueof Z = 2,221 year 2011 value of Z = 1,601 year 2012 value of Z = 1,622 year 2013 valueof Z = 1,701, PT Bina Dana Artha year 2010 value of Z = 2,015 year 2011 value of Z =1,461 year 2012 value of Z = 1,667 year 2013 value of Z = 1,840, dan PT Multhi ArthaGuna year 2010 value of Z = 2,502 year 2011 value of Z = 2,619 year 2012 value of Z =2,633 year 2013 value of Z = 2,761, showed unfavorable results are categorized intocompanies that are in the grey area and the area of bankruptcy.Keywords : Financial Ratio Analysis, Analysis of bankruptcy, Altman Z-Score Analysis,Insurance Company, Go Public